2008
DOI: 10.1094/pdis-92-9-1288
|View full text |Cite
|
Sign up to set email alerts
|

Viral Interactions Lead to Decline of Blackberry Plants

Abstract: Blackberry yellow vein disease (BYVD) poses a new threat to the blackberry industry in the United States. Blackberry yellow vein associated virus (BYVaV) was originally thought to be the sole cause of this disease. However, BYVaV has been found in several asymptomatic blackberry cultivars. An unusual member of the family Potyviridae was identified recently from symptomatic plants and named Blackberry virus Y (BVY). BVY has been shown to spread in the field and cause BYVD when co-infected with BYVaV. Both virus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(10 citation statements)
references
References 22 publications
1
9
0
Order By: Relevance
“…Several cases of synergism have been described between criniviruses and other plant viruses. BYVaV increases concentration of Blackberry virus Y (BVY, genus Brambyvirus , family Potyviridae ) in mixed infections (Susaimuthu et al, 2008). CYSDV enhanced multiplication of Cucumber vein yellowing virus (CVYV, genus Ipomovirus , family Potyviridae ) and increased symptom severity in mixed infections (Gil-Salas et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Several cases of synergism have been described between criniviruses and other plant viruses. BYVaV increases concentration of Blackberry virus Y (BVY, genus Brambyvirus , family Potyviridae ) in mixed infections (Susaimuthu et al, 2008). CYSDV enhanced multiplication of Cucumber vein yellowing virus (CVYV, genus Ipomovirus , family Potyviridae ) and increased symptom severity in mixed infections (Gil-Salas et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…It is important to note that mixed infections by two or more viruses that are latent in single infections may lead to severe symptoms or even plant mortality (17,80,96,102,103;Fig. Whereas these tolerant selections provide a potential means of circumventing the effects of infection, their use is problematic as they may display symptoms during field growth and production, induce a synergistic response when infected with other pathogens, or serve as a reservoir of infection that may be transmitted to other, less tolerant genotypes.…”
Section: The Unique Challenges For the Detection And Control Of Systementioning
confidence: 99%
“…Symptoms of BYVD only occur when blackberry plants are infected with more than one virus. Symptoms include vein yellowing, oak-leaf or irregular patterns of chlorosis, ringspots, and line patterns ( Figure 3 ; Susaimuthu et al, 2007, 2008). Floricanes can also be severely affected leading to misshapen fruit and cane dieback.…”
Section: Group-1mentioning
confidence: 99%
“…Studies have shown host-specific competition between crinivirus species that influence accumulation of other viruses present in the plant and consequently symptom severity (Karyeija et al, 2000; Susaimuthu et al, 2008; Wintermantel et al, 2008). Other viruses interact with distantly related or unrelated co-infecting viruses, resulting in increased disease severity whereas single crinivirus infections may remain asymptomatic (Karyeija et al, 2000; Tzanetakis et al, 2004, 2006b).…”
Section: Introductionmentioning
confidence: 99%